Impact of unhealthy lifestyle behaviors and obesity on CETP among adolescent boys - Hirschler, Valeria (2011)
Background and Aims Cholesteryl ester transfer protein (CETP) has been proposed to be associated with high risk of cardiovascular disease. Increased CETP activity was previously reported in obese adults, although its association with lifestyle behaviors has not been assessed in healthy adolescents. We undertook this study to determine the association between CETP activity and overweight/obesity, insulin resistance markers, components of the metabolic syndrome and lifestyle behaviors in healthy adolescent males. Methods Data were collected from 164 adolescents from an amateur rugby club. Body mass index (BMI), blood pressure (BP), Tanner stages, lipids, glucose, insulin and CETP activity were measured. Questionnaires for daily intake of breakfast, sweet drinks, milk, and hours of TV watching were completed. Results About 26% of the adolescents were obese and 23% overweight. The prevalence of metabolic syndrome was 6.7%. CETP activity was higher in obese than in normal and overweight adolescents (174 ± 35, 141 ± 30, and 149 ± 38%/ml/min, respectively; p <0.001). Univariate correlations showed an inverse association between CETP and HDL-C (r = −0.43; p = 0.018) and positive ones with BMI (r = 0.38; p = 0.007), systolic BP (r = 0.20; p <0.01) triglycerides (r = 0.40; p = 0.001), LDL-C (r = 0.46; p <0.001), TV watching >2 h/day (r = 0.17; p 0.02), and milk intake >3 glasses/day (r = 0.16; p = 0.03). Multivariate analysis showed that triglycerides, LDL-C, HDL-C, TV watching >2 h/day, milk intake >3 glasses/day and BMI were significant independent predictors for CETP (R2 = 0.41). Conclusions Unhealthy lifestyle habits such as TV watching >2 h daily and milk intake higher than three glasses per day and the increase in BMI were shown to be closely associated with high CETP activity in apparently healthy adolescent males. Future longitudinal studies should be performed to confirm these findings.